Damaged muscle fibers might masquerade as hybrid fibers – a cautionary note on immunophenotyping mouse muscle with mouse monoclonal antibodies - Morium Begam; Joseph A. Roche (European Journal of Histochemistry, 2018)
We report that, labeling mouse muscle tissue, with mouse monoclonal antibodies specific to slow or fast myosin heavy chain (sMyHC and fMyHC, respectively), can lead to artefactual labeling of damaged muscle fibers, as hybrid fibers (sMyHC+ and fMyHC+).  We demonstrate that such erroneous immunophenotyping of muscle may be avoided, by performing colabeling or serial-section-labeling, to identify damaged fibers. The quadriceps femoris muscle group (QF) in 7-month-old, male, C57BL/6J mice had: 1.21 ± 0.21%, 98.34 ± 1.06%, 0.07 ± 0.01%, and 0.53 ± 0.85% fibers, that were, sMyHC+, fMyHC+, hybrid, and damaged, respectively.  All fibers in the tibialis anterior muscle (TA) of 3-month-old, male, C57BL/6J mice were fMyHC+; and at 3 days after injurious eccentric contractions, there was no fiber-type shift, but ~ 18% fibers were damaged.